Treatment Pattern of Antiepileptic Drugs in Pediatric with Epilepsy - Dwajani S; Meghana KS; Krithika S; Adarsh E (Pharmacology and Clinical Pharmacy Research, 2021)
Studying drug utilization helps to develop twin concepts for therapeutic formulation and essential drug lists. The main preference of using Antiepileptic drug (AED) therapy is that patients can be seizure-free for their lifetime. Treating children with epilepsy remains a major challenge, despite having several AEDs. Hence, we aimed to study drug utilization patterns among pediatric patients with epilepsy. This prospective study was conducted on 150 patients lesser than 18 years of age, receiving antiepileptic drugs. A specially designed case record form was used to collect the data on socioeconomic status, disease data, and treatment details. The majority of the children were females (60.6%), ages ranged from day 1 to 4 years (56.6%). About 35.33% were skilled laborers followed by 32.23% semi-skilled. Around 49.3% of patients belonged to the lower-middle-class family and 41.33% were diagnosed to have generalized tonic-clonic seizures (GTCS). The majority of the children were on monotherapy (81.33%) while 18.66% were on dual therapy or polytherapy. Regarding the usage of antiepileptic drugs, we found that 70.66% of children were on older AEDs like sodium valproate (27.33%) followed by clobazam (31.33%). Levetiracetam was the only new antiepileptic drug that was prescribed in 10% of patients. Monotherapy is considered as best modality, due to its low cost, safety profile, and lesser drug interactions. It can also improve drug treatment compliance and adherence. Along with older AEDs, there has been an increase in the utilization of newer AEDs, which help to broaden the therapeutic option towards the management of childhood epilepsy with a better safety profile.